With Gratitude from RHiME: Reviewers 2021 - RHiME, Editor (Research and Humanities in Medical Education, 2022)
The Editorial Board of RHiME would like to thank the following experts for their outstanding contribution to the work of the journal. Without their expertise and the time they devoted to the evaluation of submissions made to RHiME, it would have been impossible to maintain the standards of the journal. Abhishek Anicca Akanksha Agrawal Anubhuti Dubey Aqsa Shaikh Arjun Ravishankar Biswaranjan Paital Devender Verma Gayatri Bhatia Jagriti Gangopadhyay Kirtana Nayak Kirti Ranchod Manjulika Vaz Mariella Scerri Maryam Golafshani Navjeevan Singh Pooja Priyamvada Radhika Kannan Roshni Babu Sambit Dash Satendra Singh Seetharaman Iyer Shalini Mullick Sheela Jaywant Sucheta Tiwari Sunita Sheel Upreet Dhaliwal Vijay Rajput Vina Vaswani Vinayak Jain